Chemical etching of manganese oxides for electrocatalytic oxygen reduction reaction1. Issue 58 (25th July 2015) - Lei, Kaixiang; Han, Xiaopeng; Hu, Yuxiang; Liu, Xue; Cong, Liang; Cheng, Fangyi; Chen, Jun
<x xml:space="preserve">Abstract</x> Mixed-valent MnOx obtained by chemically etching MnO/Mn2O3 with ceric ammonium nitrate exhibits enhanced electrocatalytic activity toward oxygen reduction.